2016
DOI: 10.1016/j.ejpb.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated fatty acids lactose esters: cytotoxicity, permeability enhancement and antimicrobial activity

Abstract: 13Sugar based surfactants conjugated with fatty acid chains are an emerging broad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…Lipozyme ® (0.078 g) was added to a solution of the fatty acid ( 1a – d ) (0.79 mmol) and 4- O -(3′,4′- O -isopropylidene-β-D-galactopyranosyl)-2,3:5,6-di- O -isopropylidene-1,1-di- O -methyl-D-glucopyranose (lactose tetra acetate, LTA) [ 26 ] ( 2 ) (0.402 g, 0.79 mmol) in water-saturated toluene at 25 °C [ 12 , 27 ]. The mixture was stirred at 75 °C for 12 h, cooled and diluted with acetone, then the enzyme was filtered, and the filtrate was concentrated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipozyme ® (0.078 g) was added to a solution of the fatty acid ( 1a – d ) (0.79 mmol) and 4- O -(3′,4′- O -isopropylidene-β-D-galactopyranosyl)-2,3:5,6-di- O -isopropylidene-1,1-di- O -methyl-D-glucopyranose (lactose tetra acetate, LTA) [ 26 ] ( 2 ) (0.402 g, 0.79 mmol) in water-saturated toluene at 25 °C [ 12 , 27 ]. The mixture was stirred at 75 °C for 12 h, cooled and diluted with acetone, then the enzyme was filtered, and the filtrate was concentrated.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have recently reported the synthesis and possible applications of selective 6- O -sugar fatty acid monoesters, generally referred as sugar monoesters [ 7 , 8 , 9 ]. Several physico-chemical and biological properties have been studied [ 10 , 11 ], to develop advanced drug delivery systems, including skin penetration enhancing effect or transmucosal permeability enhancement [ 12 , 13 , 14 , 15 ]. The use of amphiphilic compounds as permeability enhancers (PEs) for transmucosal drug delivery represents one of the most promising application of surfactants in biopharmaceutics, able to provide a valid alternative (e.g., oral or pulmonary administration) to the conventional (e.g., injection) route of administrations of many therapeutic peptides [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…General Procedure for the Synthesis of Lactose Fatty Acid Ester Derivatives (3a-e) Lipozyme ® (0.078 g) was added to a solution of the opportune fatty acid (1a-e) (0.79 mmol) and 4-O-(3',4'-O-isopropylidene-α-d-galactopyranosyl)-2,3:5,6-di-O-isopropylidene-1,1-di-O-methyl-Dglucopyranose (lactose tetra acetal, LTA)[45] (2) (0.402 g, 0.79 mmol) in dry toluene (0.5 mL) at 30 • C[46,47]. The mixture was stirred at 75 • C for 12 h, cooled and diluted with acetone, then the enzyme was filtered and the filtrate was concentrated.…”
mentioning
confidence: 99%
“…The initial microbial experiment showed that MIC (or Minimum bactericidal concentration-MBC) values of both unmodified and modified PHA monomers and their glucose esters are in most cases higher than 500 µg mL −1 , which is 50,000 fold higher than commonly used antibiotics (Ciplofloxan, Fluxonazole) [38,39]. Nevertheless, the literature reports and our results show that SFAEs in general have a bacteriostatic effect if present in higher concentrations, which can be used for other than therapeutic purposes (e.g., in the cosmetic or food industries, as surfactants/emulsifiers) [20,21,40,41]. Therefore, we increased the tested concentrations up to 5000 µg mL −1 (Table 3).…”
Section: Antimicrobial Testingmentioning
confidence: 53%